Muslim Everyday Religious Practices in Austria. From Defensive to Open Religiosity - Kolb, Jonas (Religions, 2019)
Although Muslim groups in the population comprise an integral component of Austrian society, the public image of Islam tends to be generally negative. In the meantime, there are now significant successor generations of Muslims who, in contrast with their parents' generation, have other religious orientations and positionings, and have become hybrid, heterogeneous individuals with 'multiple-home' attachments living in Austria. Nonetheless, in public discourse, they appear as a homogeneous group. Our study is based on a change in perspective, shifting front and center the religious orientation of these persons as seen from their own perspective and experiences. The findings of our study on Muslim diversity in Austria show just how differentiated, complex, ambivalent, and hybrid the everyday religious practice of individuals directly on the ground is or can be. In the following article, the focus is on a form of open religiosity that is practiced above all by members of the successor generations.